PENGARUH MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA TERHADAP MOTIVASI DAN HASIL BELAJAR MATERI SISTEM PENCERNAAN MANUSIA: Studi Eksperimen pada Siswa Kelas V MI Miftahul Huda Pandantoyo - Kartikasari, Galuh (LP2M IAIN Tulungagung, 2016)
The human digestive system material is one of the materials which close to the students. However, students cannot know directly without a guide, because of the difficulty to bring a concrete manifestation of the material. Motivation in learning is needed to support the achievement of maximum learning outcomes.The motivation can arise through learning source or learning instrument, for example, multimedia-based learning media. The calculation result of observation showed a higher increase in the experimental class, ie 30 > 27 from the number of calculations observation sheet items. The results of pre-test and post-test showed an average increase that was higher in the experimental class, in amount of 63 (pre-test) and 86.16 (post-test), grade control by 61.52 (pre-test) and 79.30 (post-test). Experimental class showed an increase learning outcomes which is higher than the control class, which is 23.26 > 17.78 fromthe difference between pre-test and post-test.Keywords: Multimedia, Motivation, Result of Study